Vehicle ride enhancement using simulation assisted rubber mount design. (20th February 2004) - Abdollahi, M.; Olatunbosun, O.A.
The work reported here describes the results of a series of parameter studies to investigate the relative effects of varying each suspension component parameter on vehicle ride comfort. The vehicle sprung mass was identified as having a significant effect on the overall ride index. A methodology is prescribed by which the ride performance of a vehicle with a passive suspension arrangement could be maintained at a predetermined limit irrespective of the vehicle load condition by suitable design of the suspension strut rubber mounts.